Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve for the inverse function [tex]\( f^{-1}(x) \)[/tex] of the given function [tex]\( f(x) \)[/tex], let's examine the function [tex]\( f(x) \)[/tex] closely.
First, let's clarify the given function. The function stated is:
[tex]\[ f(x) = 10^2 + 1 \][/tex]
In this form, [tex]\( f(x) \)[/tex] is a constant function because it does not contain the variable [tex]\( x \)[/tex] at all. Calculating the expression:
[tex]\[ f(x) = 10^2 + 1 = 100 + 1 = 101 \][/tex]
So, [tex]\( f(x) = 101 \)[/tex]. This means that for any value of [tex]\( x \)[/tex], the output is always 101.
However, typically when asking for the inverse of a function, we usually want to find a function [tex]\( g(y) \)[/tex] such that if [tex]\( y = f(x) \)[/tex], then [tex]\( x = g(y) \)[/tex]. Since [tex]\( f(x) \)[/tex] is a constant function and doesn't change with [tex]\( x \)[/tex], it doesn't have an inverse function in the usual sense. An inverse function essentially "reverses" the effect of the original function.
But let's assume there was a mistake or ambiguity in the problem statement and that the intended function was actually:
[tex]\[ f(x) = 10^x + 1 \][/tex]
In this case, we can proceed to find the inverse function:
1. Start with [tex]\( y = f(x) \)[/tex]:
[tex]\[ y = 10^x + 1 \][/tex]
2. Subtract 1 from both sides to isolate the exponential term:
[tex]\[ y - 1 = 10^x \][/tex]
3. Take the logarithm base 10 of both sides to solve for [tex]\( x \)[/tex]:
[tex]\[ \log_{10}(y - 1) = x \][/tex]
So the inverse function, [tex]\( f^{-1}(x) \)[/tex], in terms of [tex]\( x \)[/tex], is:
[tex]\[ f^{-1}(x) = \log_{10}(x - 1) \][/tex]
Therefore, the correct answer is:
[tex]\[ f^{-1}(x) = \log (x - 1) \][/tex]
First, let's clarify the given function. The function stated is:
[tex]\[ f(x) = 10^2 + 1 \][/tex]
In this form, [tex]\( f(x) \)[/tex] is a constant function because it does not contain the variable [tex]\( x \)[/tex] at all. Calculating the expression:
[tex]\[ f(x) = 10^2 + 1 = 100 + 1 = 101 \][/tex]
So, [tex]\( f(x) = 101 \)[/tex]. This means that for any value of [tex]\( x \)[/tex], the output is always 101.
However, typically when asking for the inverse of a function, we usually want to find a function [tex]\( g(y) \)[/tex] such that if [tex]\( y = f(x) \)[/tex], then [tex]\( x = g(y) \)[/tex]. Since [tex]\( f(x) \)[/tex] is a constant function and doesn't change with [tex]\( x \)[/tex], it doesn't have an inverse function in the usual sense. An inverse function essentially "reverses" the effect of the original function.
But let's assume there was a mistake or ambiguity in the problem statement and that the intended function was actually:
[tex]\[ f(x) = 10^x + 1 \][/tex]
In this case, we can proceed to find the inverse function:
1. Start with [tex]\( y = f(x) \)[/tex]:
[tex]\[ y = 10^x + 1 \][/tex]
2. Subtract 1 from both sides to isolate the exponential term:
[tex]\[ y - 1 = 10^x \][/tex]
3. Take the logarithm base 10 of both sides to solve for [tex]\( x \)[/tex]:
[tex]\[ \log_{10}(y - 1) = x \][/tex]
So the inverse function, [tex]\( f^{-1}(x) \)[/tex], in terms of [tex]\( x \)[/tex], is:
[tex]\[ f^{-1}(x) = \log_{10}(x - 1) \][/tex]
Therefore, the correct answer is:
[tex]\[ f^{-1}(x) = \log (x - 1) \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.